2021
DOI: 10.1002/smi.3060
|View full text |Cite
|
Sign up to set email alerts
|

Stress and COVID‐19 related behaviours: The mediating role of delay discounting

Abstract: We examined stress as a predictor of behaviours related to Coronavirus Disease‐2019 (COVID‐19) through its effects on delay discounting. Adults ( N = 3686) completed an online survey with a behavioural measure of delay discounting and questions regarding stress, physical distancing, and stockpiling of food and supplies. Stress was weakly, but positively, correlated with delay discounting ( p < 0.01). Delay discounting was positively correlated with stockpiling ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…First, the study was conducted on a very specific population of university students and this may pose some limitations in terms of generalization of the results. Secondly, while recent research has found results in line with those reported here [42], other studies have found the opposite pattern, namely that steeper delay discounting predicted poorer adherence to social distancing measures [43,44]. Therefore, further studies are necessary to better understand the relationship between adherence to containment measures and preferences in discounting behavior.…”
Section: Discussionmentioning
confidence: 45%
“…First, the study was conducted on a very specific population of university students and this may pose some limitations in terms of generalization of the results. Secondly, while recent research has found results in line with those reported here [42], other studies have found the opposite pattern, namely that steeper delay discounting predicted poorer adherence to social distancing measures [43,44]. Therefore, further studies are necessary to better understand the relationship between adherence to containment measures and preferences in discounting behavior.…”
Section: Discussionmentioning
confidence: 45%
“…Delay discounting has been associated with stress ( Malesza 2019 ), including during the pandemic, ( Craft et al. 2021 ; DeAngelis et al. 2021 ), which has been a source of stress ( Charles et al.…”
Section: Discussionmentioning
confidence: 99%
“…Although correlational studies suggest that stress can be associated with greater delay discounting during COVID-19 ( Malesza 2019 ; Lloyd et al. 2021 ; DeAngelis et al. 2021 ), there is limited insight regarding possible changes in delay discounting that may accrue with ongoing COVID-19 stress.…”
Section: Introductionmentioning
confidence: 99%
“…The extent to which delay discounting is a predictor of compliance with pandemic-mitigating behaviors other than vaccination (e.g., physical distancing, mask-wearing) is less clear 34 36 . Seemingly weak or contradictory findings may reflect the influence of confounding factors, such as psychological distress, which tends to be positively related to delay discounting 37 . Given the association between psychological distress and delay discounting 23 , it is perhaps not surprising that psychological distress did not predict vaccination status after controlling for other variables.…”
Section: Discussionmentioning
confidence: 99%